1983
DOI: 10.21273/hortsci.18.2.247
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Triacontanol on the Growth and Development of Tabasco Pepper

Abstract: Triacontanol (1-hydroxytriacontane) applied as a soil drench 18 and 43 days after planting increased the plant height of 71-day-old seedlings of Tabasco pepper (Capsicum frutescens L.) in a greenhouse experiment. Triacontanol applied as a soil drench at transplanting significantly increased early maturity, total yield, and number of fruits in the field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1983
1983
2005
2005

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In studies with ir rigated and nonirrigated field maize Regehr (60) showed a minimal effect of TRIA on maize yield, and suggested that the incon sistent performance of TRIA in the field should not be attributed to the environmental con ditions of the growing crops. TRIA applied as a soil drench has been shown to be effec tive in promoting the growth and develop ment of tabasco pepper (Capsicum frutescens) both in the greenhouse and field (47). Others found no increase in yield of muskmelons (Cucumis meld) (5), or sweet potatoes (Ipomoea batatas) (6).…”
Section: Crop Yieldmentioning
confidence: 99%
“…In studies with ir rigated and nonirrigated field maize Regehr (60) showed a minimal effect of TRIA on maize yield, and suggested that the incon sistent performance of TRIA in the field should not be attributed to the environmental con ditions of the growing crops. TRIA applied as a soil drench has been shown to be effec tive in promoting the growth and develop ment of tabasco pepper (Capsicum frutescens) both in the greenhouse and field (47). Others found no increase in yield of muskmelons (Cucumis meld) (5), or sweet potatoes (Ipomoea batatas) (6).…”
Section: Crop Yieldmentioning
confidence: 99%